The Re:Search Engine: Simultaneous Support for Finding and Re-Finding - Teevan, Jaime (Proceedings of UIST, 2007)
Re-finding, a common Web task, is difficult when previously viewed information is modified, moved, or removed. For example, if a person finds a good result using the query “breast cancer treatments”, she expects to be able to use the same query to locate the same result again. While re-finding could be supported by caching the original list, caching precludes the discovery of new information, such as, in this case, new treatment options. People often use search engines to simultaneously find and re-find information. The Re:Search Engine is designed to support both behaviors in dynamic environments like the Web by preserving only the memorable aspects of a result list. A study of result list memory shows that people forget a lot. The Re:Search Engine takes advantage of these memory lapses to include new results where old results have been forgotten.